Pengaruh Perencanaan Pajak Beban Pajak Tangguhan Cash Effective Tax Rate Terhadap Persistensi Laba Perusahaan Non Cyclical - Saputri, Denya; I, Istianinngsih; Husadha, Cahyadi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to analyze the effect of tax planning, deferred tax burden, and Cash Effective Tax Rate on profit persistence. The object of this study is non-cyclical consumer companies listed on the Indonesia Stock Exchange in the period 2020 - 2022. This type of research is quantitative research, using a population of 86 companies listed on the Indonesia Stock Exchange in the non-cyclical sector. The sampling method in this study uses the purposive sampling method, based on the selected criteria, the number of samples used is 118 samples as observations. The data source used in this study is secondary data obtained from www.idx.co.id to obtain data in the form of financial reports from each company, then the data is processed using the SPSS version 25 program. The results of the research conducted, the author can conclude that: (1) Tax Planning has a negative effect on Profit Persistence, (2) Deferred Tax Burden does not affect Profit Persistence, (3) Cash Effective Tax Rate has a negative effect on Profit Persistence.